Tre grandi traduttori: Poggioli, Traverso e Bo - Lucidi, Alceo (Linguæ & - Journal of Modern Languages and Cultures, 2024)
To look back over the history of translation is always a very complicated question, especially if a professional status of the translator all along the past times has still to be focused and investigated and not been found yet. Starting from the beginning of the 20th century and the involvement of intellectuals as writers, essayists as well as translators in the relevant city of Florence, three main scholars and protagonists of the cultural debate during the Italian fascist regime, such as Renato Poggioli, a specialist of Russian language and culture, Leone Traverso, a classical and German philologist and Carlo Bo, a huge expert in the Spanish and French linguistic domains, were analyzed to fix their contribution to a better understanding of a still misty word: translation.